Społeczeństwo wiedzy i organizacje wiedzy. O roli menedżerów w nowoczesnych procesach społecznych - Banaszak, Sławomir (Studia Edukacyjne, 2020)
Managers are very important part of modern organizations and societies. The paper is an attempt at showing managers as a factor of creating knowledge organizations. The author points at qualifictions and competences of managers as the main issue in this process. Problems of “knowledge production” and “knowledge processing” are revealed. The paper ends with the approach to the problems of economic efficiency of knowledge and its positive impact on organizations and societies.